2014
DOI: 10.1103/physrevlett.113.123001
|View full text |Cite
|
Sign up to set email alerts
|

Confirming a Predicted Selection Rule in Inelastic Neutron Scattering Spectroscopy: The Quantum Translator-RotatorH2Entrapped InsideC60

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk AbstractWe report an inelastic neutron scattering (INS) study of H 2 molecule encapsulated inside the fullerene C 60 which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…For example, several nanoconfined molecules exhibit new set of states, as a result of strong couplings between rotational and translational motions, and new selection rules have been applied to identify observed spectral peaks with respect to those of an isolated molecule. 27,31 Although, much has been learned about characterizing quantum confinement of molecular nuclear motion, several aspects of these features are still not fully understood. This is the case of the endohedral water fullerene (H 2 O@C 60 ) complex, which has been recently synthesized, 25 and then characterized spectroscopically by INS, FIR and NMR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several nanoconfined molecules exhibit new set of states, as a result of strong couplings between rotational and translational motions, and new selection rules have been applied to identify observed spectral peaks with respect to those of an isolated molecule. 27,31 Although, much has been learned about characterizing quantum confinement of molecular nuclear motion, several aspects of these features are still not fully understood. This is the case of the endohedral water fullerene (H 2 O@C 60 ) complex, which has been recently synthesized, 25 and then characterized spectroscopically by INS, FIR and NMR techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the 3 He case, an NMR signal of He 3 was observed [62]. Another practical method for detecting such complexes is the rotational-vibrational spectroscopy, which allows some nonstandard peculiarities in the spectra to be revealed [63]. In 1997, Saunders et al experimentally observed He 2 @C 60 [64] (see also works [65,66]); and, later, Ng @C 60 with = 2 [67][68][69][70].…”
Section: Aristotlementioning
confidence: 99%
“…The carbon atom can be inside or outside the cage, and different spectra exist for these different spatial regions. Although this system is a very simple one, it has practical relevance in that the trapping of various atoms and molecules within fullerene cages is currently being investigated with a range of applications in mind, from drug delivery [23][24][25], to nanomaterials design [26], and to a new type of trap for single atom physics experiments [27].…”
Section: Equation Although In 1912mentioning
confidence: 99%